Hadith #57 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
I gave the pledge of allegiance to Allah’s Messenger (ﷺ) for the following: 1. offer prayers perfectly 2. pay the Zakat (obligatory charity) 3. and be sincere and true to every Muslim.
Grade: Sahih

Hadith #514 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
I gave the pledge of allegiance to Allah’s Messenger (ﷺ) for to offer prayers perfectly, to pay Zakat regularly, and to give good advice to every Muslim.
Grade: Sahih

Hadith #560 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
We were with the Prophet (ﷺ) on a full moon night. He looked at the moon and said, “You will certainly see your Lord as you see this moon, and there will be no trouble in seeing Him. So if you can avoid missing (through sleep, business, etc.) a prayer before the rising of the sun (Fajr) and before its setting (`Asr) you must do so. He (the Prophet (ﷺ) ) then recited the following verse: And celebrate the praises Of Your Lord before The rising of the sun And before (its) setting.” (50.39)
Grade: Sahih

Hadith #1354 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
I gave the pledge of allegiance to the Prophet (ﷺ) for offering prayer perfectly, giving Zakat, and giving good advice to every Muslim.
Grade: Sahih

Hadith #3659 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) has never refused to admit me since I embraced Islam, and whenever he saw me, he would smile.
Grade: Sahih

Hadith #3660 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
There was a house called Dhul-Khalasa in the Pre-lslamic Period and it was also called Al-Ka’ba Al-Yamaniya or Al-Ka’ba Ash-Shamiya. Allah’s Messenger (ﷺ) said to me, “Will you relieve me from Dhul-Khalasa?” So I left for it with 150 cavalrymen from the tribe of Ahmas and then we destroyed it and killed whoever we found there. Then we came to the Prophet (ﷺ) and informed him about it. He invoked good upon us and upon the tribe of Ahmas.
Grade: Sahih

Hadith #4644 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
We were in the company of the Prophet (ﷺ) on a fourteenth night (of the lunar month), and he looked at the (full) moon and said, “You will see your Lord as you see this moon, and you will have no trouble in looking at Him. So, whoever can, should not miss the offering of prayers before sunrise (Fajr prayer) and before sunset (`Asr prayer).” Then the Prophet (ﷺ) recited: ‘And celebrate the praises of your Lord before the rising of the sun and before (its) setting.’ (50.39)
Grade: Sahih

Hadith #5785 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
The Prophet (ﷺ) said, “He who is not merciful to others, will not be treated mercifully.
Grade: Sahih

Hadith #7095 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Allah will not be merciful to those who are not merciful to mankind.”
Grade: Sahih

Hadith #7151 - Sahih al-Bukhari - Jarir bin 'Abdullah al-Bajli (Sahih al-Bukhari)
The Prophet (ﷺ) said, “You will definitely see your Lord with your own eyes.”
Grade: Sahih